2020
DOI: 10.1093/nar/gkaa485
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and development-stage–specific mRNA and heterogeneous CNV signatures of human ribosomal proteins in normal and cancer samples

Abstract: We give results from a detailed analysis of human Ribosomal Protein (RP) levels in normal and cancer samples and cell lines from large mRNA, copy number variation and ribosome profiling datasets. After normalizing total RP mRNA levels per sample, we find highly consistent tissue specific RP mRNA signatures in normal and tumor samples. Multiple RP mRNA-subtypes exist in several cancers, with significant survival and genomic differences. Some RP mRNA variations among subtypes correlate with copy number loss of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 58 publications
0
47
0
Order By: Relevance
“…In addition, Feng et al found that RPL14(eL14) promoted cancer invasion and migration in cervical cancer [12]. All these data not only indicated that the expression of RPL14(eL14) may have specific tissue heterogeneity [31,32] but also effectively confirm that RPL14(eL14) may serve as an important regulator in tumor progression.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, Feng et al found that RPL14(eL14) promoted cancer invasion and migration in cervical cancer [12]. All these data not only indicated that the expression of RPL14(eL14) may have specific tissue heterogeneity [31,32] but also effectively confirm that RPL14(eL14) may serve as an important regulator in tumor progression.…”
Section: Discussionmentioning
confidence: 89%
“…Ribosomal proteins are abnormally expressed in a variety of tumors, which affect the apoptosis, aging, growth, invasion, drug and radiation resistance [75]. The expression level of ribosomal protein has become a potential indicator of tumor diagnosis, treatment and prognosis [76]. Bioscience Reports.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal proteins are abnormally expressed in a variety of tumors, which affect the apoptosis, aging, growth, invasion, drug and radiation resistance [ 75 ]. The expression level of ribosomal protein has become a potential indicator of tumor diagnosis, treatment and prognosis [ 76 ]. Through the in-depth study of abnormal expression and ubiquitination modification of ribosomal proteins in tumor tissue, we can further understand the role of high expression of ribosomal protein gene in malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomopathies are pathologies which result from mutations in certain RP genes ( Orgebin et al, 2020 ), with as many as 20 RP genes, including RPS19, involved in Diamond-Blackfan anaemia (DBA) ( Leger-Silvestre et al, 2005 ; Da Costa et al, 2020 ). Besides a deficiency of erythroblasts, about 50% of DBA patients experience other congenital anomalies such as growth retardation, cardiac and urogenital abnormalities, increased risk of cancer, cephalic malformations and learning difficulties ( Da Costa et al, 2020 ; Panda et al, 2020 ). Fragile-X syndrome is another well-characterised neurodevelopmental disorder associated with intellectual disability and learning difficulties.…”
Section: Translation Regulation Through Heterogeneous Ribosomesmentioning
confidence: 99%